Application of Reliability Simulation Based on Monte Carlo Method in GNSS Receiver. Issue 4 (June 2021) - Liu, Ningbo; Guan, Yu; Liu, Xianyang; Liu, LiHong; Wang, Haiyue
Abstract: At present, the analytical method (reliability prediction) is mainly used to calculate the equipment reliability of electronic equipment system. But reliability verification and evaluation of electronic equipment, which is highly reliable, needs a lot of time and economic costs. In this paper, a reliability simulation algorithm based on Monte Carlo method is proposed to verify and evaluate the reliability of highly reliable GNSS receiver. Which can meet the requirements and greatly reduce the project cost.